Analysis of the Influence of Service Quality on Sharia Customer Loyalty at Social Security Administrator for Employment (BPJS Ketenagakerjaan) Banda Aceh Branch Office - Rufani, Marina; Ridwan, Muhammad; Samri Julianti Nasution, Yenni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to examine the effect of tangibles, reliability, responsiveness, assurance andempathypartially and simultaneously on customer loyalty at the Social Security Administrator for Employment (BPJS Ketenagakerjaan) Banda Aceh Branch Office. This type of research is associative quantitative research using multiple linear regression analysis with a sample of 100 people. The research results show that. Partially and simultaneously tangibles (direct/ physical evidence), reliability, responsiveness, assurance (guarantee), and Empathy (attention) have an influence on customer loyalty in choosing Social Security Administrator for Employment (BPJS Ketenagakerjaan) in Banda Aceh. It can be seen from F-count > F-table or 15.598 > 2.311 with a determinant value of the multiple correlation coefficient of 0.903 is positive, meaning that the tangibles, reliability, responsiveness, and assurance variables have a very strong influence on empathy. or 90.3%.